Single-Molecule Analysis of Alkaline Phosphatase - Douglas B. Craig (Kinases and Phosphatases)
Chemical studies usually consist of measurements made on large ensembles of molecules with data representing average values for the population. It has been shown that individual molecules of a given enzyme have different properties. Large-scale averaging has in the past masked these differences. Alkaline phosphatase has been used as a model to study this enzyme heterogeneity. The catalytic rates of the individual molecules have been found to differ by over 10-fold, and the activation energy of catalysis by more than two-fold. Differences in properties indicate that differences in structure must exist between the molecules. For alkaline phosphatase, the structural differences have been suggested to be differences in glycosylation, differences due to partial proteolysis, and due to some molecules containing mixtures of active and inactive subunits. The determination of the distribution of activities of populations of this enzyme within a sample has also been shown to be a useful tool in diagnostics. This review discusses the advent of single-molecule enzymology and summarizes its use in the study of alkaline phosphatase using capillary electrophoresis, microscopic well assays, and single-molecule tracking.